Caring for Colour: Multispecies Aesthetics at the Great Barrier Reef - Quigley, Killian (Queensland Review, 2021)
The Great Barrier Reef has been bleaching yet again. If the Anthropocene had a colour table, bleached coral would hold an especially recognizable place within it. By some lights, chromatic behaviour — and chromatic disaster — are best apprehended as secondary qualities, as spectacles that offer to point the discerning observer beyond the tokens of human sense and toward an object’s (or ecosystem’s) essential properties. This article asks whether it is possible, and ethically viable, to recognise corallian colour practice as having meaning in and of itself. I argue that we should recognise coral colourism as the irreducibly relational comportment of species, sunlight, salt water, sediment and so on. Contrary to some influential views, the Reef’s performances are not simply constructed by the fantasies of human spectators, but by stimulating human sensoria, they do hail us as participants in the chromatic field. Reckoning the loss of hue as a discrete catastrophe might therefore generate tools for articulating value in a manner that is not strictly constructivist, naively scientistic or reactionarily idealistic. Caring for the Reef may be, not first of all but not least of all, a caring for colour — a caring against chromatic disappearance and a caring towards chromatic repair.